IMPROVING THE DEFINITION OF THE IMAGE OF THE TRAIN SITUATION USING THE METHOD OF SAATY (Transport systems and technologies, 2018)
In the process of train control driver processes a large amount of operational information. The task of developing the theoretical foundations of pattern recognition train situations is important and requires detailed development. As a result of the analysis of the activities of the driver obtained an indicative list of situations that arise in the management of a locomotive that has twelve items. It build on the hierarchy of train situations and the resultant groups: safe driving mode, driving mode, requiring high attention, dangerous driving mode. All groups of criteria, the actual criteria and options are compared witheach other according to the scheme «with each other», the results of the comparison are presented in the form of a matrix of paired comparisons. For each matrix of pairwise comparisons is formed vector of weighting coefficients. With each pairwise comparison matrix obtained separate weight vector – the number of available train situations. The result of multiplying all matrices is a vector (single column matrix) containing the weights of such options. Thus obtained values of weight coefficients of criteria for the three groups and the closing odds. Using this approach, you can most accurately determine the current state of the system «locomotive crews-train» and to prepare the most appropriate controldecision.
Keywords: decision making, image of the situation, the locomotive, the engineer, intelligent system